Analisis Tingkat Produktivitas Produksi Sparepart Motor Footstep Menggunakan Metode Objective Matrix (OMAX) dan Root Cause Analysis (RCA) Pada UMKM Imvspeedshop - Ramadani, Moch; Rosyidi, Khafizh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study evaluates the productivity of footstep-type motorcycle spare part production at UMKM IMVSPEEDSHOP Pasuruan, where production capacity fails to meet market demand. The Objective Matrix (OMAX) method was employed to assess productivity across five key performance ratios, while Root Cause Analysis (RCA) incorporating Fishbone Diagram and 5-Why’s Analysis identified underlying inefficiencies. The Analytical Hierarchy Process (AHP) prioritized critical factors affecting productivity. Findings revealed fluctuating productivity levels, with Ratio 5 (labor hours per defective unit) scoring lowest (43), highlighting inefficiencies in defect control. Major contributing factors included insufficient operator training, irregular machine maintenance, lack of standardized procedures (SOP), and suboptimal workspace design. Proposed corrective measures encompass developing comprehensive SOPs, enhancing technical training, implementing preventive maintenance schedules, and optimizing ergonomic conditions. These interventions aim to boost operational efficiency, reduce waste, and align production output with market requirements. The study provides actionable insights for improving productivity in small-scale automotive manufacturing, offering a framework for similar MSMEs facing comparable challenges.